Designing Bank Building 10 Floors With 1 Basement Using Partial Ductile System In Surakarta - Ashari, Farid Tegar, Ir. H. Suhendro Trinugroho, M.T, H. Budi Setiawan, ST. M.T (2015)
Final project is meant to plan a reinforced concrete structure 10 with 1 basement floor, which is the building to the bank of the region Surakarta (earthquake region 3) which stands on solid ground and is based on ISO 1726-2002 with the value of ductility factor (μ) = 2.5 that includes the partial ductile. The purpose of this thesis is to obtain a comparison or efficiency of the planning structure based on the three dimension building, which includes structural mechanics analysis, the distribution of shear loads or seismic and needs reinforcement. Design of reinforced concrete structures using quality materials that include concrete quality f'c = 25 MPa, the quality of steel fy = 300 MPa and frame the horses using quality steel used Bj 41. Regulation as reference includes PPIUG-1983, SNI 03-1729- 2002, PPBBI-1984, PBI-1971, SNI 03-2847-2002. Analysis of structural mechanics using "SAP 2000 v.14" 3 dimension. Mathematical calculations using the "Microsoft Excel 2007". While the depiction using "AutoCAD 2007". The results of final project as follows : 1). Roof structure using steel frame frame profile 2L50x50x5 and 2L50x50x6. 2). The thickness of plate floor (1-9) 12 cm with main reinforcement D10 and divisor reinforcement dp8. To plate used stairs and landing plate 12 cm thick with main reinforcement D12 and divisor reinforcement dp8. 3). Beams with dimensions 400/700 mm with main reinforcement D22 and shear reinforcement 2dp8. Column with dimensions 500/500 mm with main reinforcement D25 and shear reinforcement 2dp10. 4). Pile cap using size 4x4 m2 thick 100 cm with reinforcement D25-100 mm. Piles with dimensions 35 / 35 cm with the main reinforcement 4D22 and shear reinforcement 2dp10-140.